2010
DOI: 10.1097/aog.0b013e3181e3e7e8
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Thickness Measurement for Detecting Endometrial Cancer in Women With Postmenopausal Bleeding

Abstract: Previous meta-analyses on endometrial thickness measurement probably have overestimated its diagnostic accuracy in the detection of endometrial carcinoma. We advise the use of cutoff level of 3 mm for exclusion of endometrial carcinoma in women with postmenopausal bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
124
0
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(140 citation statements)
references
References 26 publications
1
124
0
15
Order By: Relevance
“…This endometrial thickness cutoff is applicable both in users and non-users of hormone replacement therapy [2]. Even though it has been suggested that it would be safer to use a cutoff of 3 mm to exclude endometrial cancer in women with postmenopausal bleeding [5], the 4 mm cutoff prevails in clinical practice.…”
Section: A Imaging Techniques In the Management Of Postmenopausal Blmentioning
confidence: 99%
“…This endometrial thickness cutoff is applicable both in users and non-users of hormone replacement therapy [2]. Even though it has been suggested that it would be safer to use a cutoff of 3 mm to exclude endometrial cancer in women with postmenopausal bleeding [5], the 4 mm cutoff prevails in clinical practice.…”
Section: A Imaging Techniques In the Management Of Postmenopausal Blmentioning
confidence: 99%
“…18 With relation to endometrial carcinoma, a recent meta-analysis suggested reducing the cutoff point for endometrial thickness measured by transvaginal ultrasonography to 3mm with the objective of increasing the method's sensitivity for ruling out neoplasms in postmenopausal women with bleeding. 19 In our study, 15 women who did have abnormal hysteroscopic findings were not identified by ultrasound screening, taking normal endometrial thickness as less than 5 mm. Notwithstanding, just six of these 15 women had histologically active endometrial lesions and no cases of hyperplasia or neoplasm were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Transvaginal ultrasonography measurement of an endometrial thickness of 5 mm or more has been shown to detect 95% of endometrial carcinomas in postmenopausal women. 8 The overlap of normal endometrial thickness with carcinoma limits the value of ultrasound in premenopausal women. Histochemical markers, e.g.…”
Section: Discussionmentioning
confidence: 99%